15.5L: Late‐News Paper: SVGA Full‐Color Bidirectional OLED Microdisplay. Issue 1 (June 2015) - Wartenberg, Philipp; Richter, Bernd; Brenner, Stephan; Thomschke, Michael; Fehse, Karsten; Baumgarten, Judith; Vogel, Uwe
Abstract : This paper describes a new bidirectional OLED microdisplay with an increased SVGA resolution. A bidirectional microdisplay means that the active area comprises of an OLED display with an additional nested image sensor. The paper shows latest results from the labs as well as first results in the field of capturing an eye scene.